Child and Adult Socioeconomic Status and the Cortisol Response to Acute Stress: Evidence From the Multi-Ethnic Study of Atherosclerosis. Issue 2 (February 2018) - Lê-Scherban, Félice; Brenner, Allison B.; Hicken, Margaret T.; Needham, Belinda L.; Seeman, Teresa; Sloan, Richard P.; Wang, Xu; Diez Roux, Ana V.
ABSTRACT: Objective: A long-hypothesized pathway through which low socioeconomic status (SES) harms health is through dysregulation of the physiologic stress response systems. No previous studies have tested this hypothesis by investigating cortisol reactivity and recovery to acute stress in relation to SES at different times in the life course in adults. Alteration of the cortisol response to an acute stressor could signal dysregulation of the hypothalamic-pituitary-adrenal axis and has been associated with chronic illness. Methods: We used data on 997 adults 54 years or older from a multiethnic, multisite United States study to examine associations between life course SES and cortisol response to a laboratory stress challenge. Informed by life course theory, we hypothesized that lower child and adult SES would be associated with lower reactivity (i.e., smaller increase in cortisol) and a slower recovery rate (i.e., slower rate of decline in cortisol after the challenge). Results: In demographics-adjusted multilevel piecewise linear regression models, low child and adult SES were associated with a 19% (95% CI = 4%–50%) and 27% (7%–55%) slower recovery rate compared with high child and adult SES, respectively. Compared with participants with stable high SES, those with stable low SES had a 48% (16%–70%) slower recovery rate. Differences in reactivity by SES were small. Conclusions: Our results support the hypothesis that low SES throughout life affects the hypothalamic-pituitary-adrenal axis and in turn the ability to recover from exposure to acute stressors. This mechanism can help explain how socioeconomic disparities contribute to disparities in chronic disease. Abstract : Supplemental digital content is available in the text.